"Children in the prison nursery": Global progress in adopting the Convention on the Rights of the Child in alignment with United Nations minimum standards of care in prisons. (December 2022) - Van Hout, Marie Claire; Fleißner, Simon; Klankwarth, Ulla-Britt; Stöver, Heino
Abstract: Background: Out of the 11 million detained in prisons globally, the female prison population of 740, 000 has increased by 50 % since 2000. 410, 000 children are in detention. 19, 000 live in prison with their mother. Objective: To conduct a socio legal assessment of global progress in adopting the Convention on the Rights of the Child since 2010, and alignment with United Nations (UN) normative standards of care in prisons. Participants and setting: Children detained with their mothers at the global level. Methods: A comprehensive search of all published Concluding Observation reports of the UN Committees on the Rights of the Child (CRC), Elimination of Discrimination Against Women (CEDAW), Against Torture (CAT) and Human Rights (CCPR) since 2010 (n = 905). 316 CRC, 246 CEDAW, 173 CAT and 170 CCPR reports were scrutinised to examine the situation of children living with detained mothers against UN normative standards of care. Results: 51 reports (24 CRC, 13 CEDAW, 12 CAT, 2 CCPR) representing 43 countries (majority in Africa) contained direct violations of the best interests of the child. These include the treatment of children as prisoners, difficulties in securing identity documents, poor detention conditions, exposure to violence, lack of access to child-appropriate healthcare, and lack of transparent data. Countries differed in durations of time permitting children to stay in prison (6 months to 8 years, with Eritrea observing no limit). Conclusions: Achieving a balance between protection of the child and punishment of the mother is inconsistent globally, and exacerbates the multiple vulnerabilities of the child.